Occupational Accident Analysis in CV. Purnama Workshop Using HAZOP (Hazard and Operability) Method - Kuswanda, Alfanny; ., Solichin; Novita Deniati, Ema (KnE Life Sciences, 2021)
CV. Purnama’s workshop is a welding workshop with appropriate technology. The workshop covers an area of 600 m2 , with a total of seven workers. The workshop manufactures a cracker-making machine, a cutting machine, a dough mixer, etc. A preliminary study on the manufacturing process of the workshop conducted in 2014 reported a work accident in which the workers’ feet were exposed to iron. Also, in 2019, workers fell into a boiler-machine pulley, which hit the head of one of the workers. Thus, this study aims to determine the risks and hazards involved in the work process at the Purnama workshop. This study used a qualitative research method and collected data through observation in each machine-building process and interviews with all workshop employees and workshop owners. The results of this study highlighted that the process of making a chopping machine had six hazards, while that of a dough mixer had five. The levels of hazards in the processes of making a chopping machine and a dough mixer were “high” at 58% and 56%, respectively. It is concluded that since a higher level of danger was found in each machine-building process in the workshop, risk control is necessary to avoid work accidents or occupational diseases. The workshop owners and workers are recommended to apply K3 in the workplace. Keywords: HAZOP, risk assessment, work accidents